O projeto observatório da educação - capes - UEA - fases da difusão do conhecimento - Branco, Anne Karynne Almeida Castelo (2014)
Study resulting from the Dissemination of the scientific knowledge produced by the Center for Education Project - POE/CAPES/UEA, developed in a Manaus public school, through experiences from researchers linked to it. It comes from the reflections of the concepts of Scientific Divulgation (DC), Scientific Communication (CC) and Scientific Diffusion, aiming the comprehension of the specificities of each one and the suitability to the research proposal. The same pervades through the CC phase, which objective is to comprehend how did the dissemination of the knowledge, resulting from the execution of the POE, taking as reference the Events, Scientific Journals, Books and Social Media. From the mapping of the POE‟s productions, along the three years of operation of the Project (2011 – 2013), collected from the reports of POE, Curriculum Lattes of the researchers, sites of the events, proceedings and journals, it was possible to identify the publications, the vehicles used for their communication and the perception of the researchers in the way of perceiving transposing the research universe when exposing their experience for their pares and to the society, besides comprehending the difficulties to disclose the generated knowledge and the possibilities foreseen, through the dissemination of their researches. We note that they possess the comprehension of the importance to take the knowledge outside of the group, which characterizes much more than the individual construction of their curriculums, passes through the strengthening of the Project itself, of the Post-graduation Program, of the University and the people engagement with themes like the interdisciplinary nature. It is the DC phase, which through the qualitative approach considered the observation of the moments in which the publishing activities of the characterizing process and products of the Scientific Process Publishing were realized. Through the observation, strategies and interventions developed on the social media (Facebook, Twitter, Blog) articulated in the formal space of the classroom, from what is proposed by the investigative communities (Portuguese Language, Mathematics and Sciences), interviews and questionnaires, we aim to understand the engagement of the subjects and their impact on the Diffusion of Science. We verified that it is necessary to pre dispose to follow the path of the counterculture, to cross the obstacles of the new and of what is already instituted for the development of inovative proposals that will bring together the university and the school